Akulturasi Islam Dan Budaya Dalam Tradisi Perkawinan Pada Masyarakat Sumbawa Nusa Tenggara Barat - Utama, Abdul Alimun; Junaidi, Junaidi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study aims to determine Islamic acculturation and culture in the marriage tradition in Sumbawa Regency. The sub-problems of the subject matter are as follows: 1. How is the procession of the wedding tradition of the community in Sumbawa Regency? 2. How is Islamic Acculturation and local culture in the marriage traditions of the people in Sumbawa Regency?. The author uses a type of cultural research by using descriptive-qualitative data analysis, which is research intended to understand phenomena or events regarding traditions carried out by research subjects that produce descriptive data in the form of oral information from several people who are considered to know better, and behavior and objects observed. The research approaches used are, the Anthropological approach, the Religy Approach, and the historical approach. Furthermore, the data collection method using Field Research, the author tries to bring up the object being talked about according to the reality that occurs in society. The results of this study show that there is a synergy between constancy in customs and religious observance. In the philosophy of life of the Sumbawa people, it is known as "Adat Berenti Ko Syara‟, Syara‟ Berenti Ko Kitabullah". This means that by making adat (adat) and syara‟ (shari'a) both as the foundation of life for the Sumbawa people, this unites the functions of the two in regulating life. Furthermore, many indigenous activities have been adapted to the principle of Islam. Islam is translated into the apparatus of local life while maintaining the existing pattern and then transformed into the essence of tawhid. This research uses this local potential as a strategy to build spirituality without character. Islam in the nuances of Sumbawa customs is interpreted into values and traditions so as to form the identity of the Sumbawa people. Finally, the encounter of customs and religions in the culture of the Sumbawa people shows that there has been a dialogue and reconstructed a new culture in local nuances.